The combination of Radix Astragali and Radix Angelicae Sinensis attenuates the IFN-γ-induced immune destruction of hematopoiesis in bone marrow cells - Juan Liu; Jie Wei; Changzhi Wang; Xiaoying Meng; Hening Chen; Peiying Deng; Meiyier Huandike; Huijie Zhang; Xue Li; Limin Chai (BMC, 2019)
Abstract Background Radix Astragali and Radix Angelicae Sinensis are two herbs that compose Danggui Buxue Tang (an herbal formula for treatment of anemia diseases). In this study, we explored the molecular mechanism and effective targets to immune destruction of bone marrow (BM) cells treated with Radix Astragali, Radix Angelicae Sinensis or a combination of two agents. The potential synergic advantages of two herbs should also be explored. Methods The constituents of Radix Astragali and Radix Angelicae Sinensis were analyzed by high performance liquid chromatography-electrospray ionization/mass spectrometer system BM cells were separated from limbs of BALB/c mice, and immune destruction was induced with IFN-γ. The percentages of hematopoietic stem cells (HSCs) and CD3+ T cells were detected by flow cytometry. The distribution of T-bet and changes in the combination of SAP and SLAM in BM cells were observed by immunofluorescence. Western blotting was used to assay the expression of key molecules of the eIF2 signaling pathway in BM cells. Results Seven constituents of Radix Astragali and six constituents of Radix Angelicae Sinensis were identified. The percentages of HSCs increased significantly after treatment with Radix Angelicae Sinensis, especially at high concentrations. The percentages of CD3+ T cells were significantly decreased after Radix Astragali and Radix Angelicae Sinensis treatment. However, the synergistic function of two-herb combinations was superior to that of the individual herbs alone. The distribution of T-bet in BM cells was decreased significantly after Radix Angelicae Sinensis treatment. The number of SLAM/SAP double-stained cells was increased significantly after Radix Astragali treatment at low concentrations. The phosphorylation levels of eIF2α were also reduced after Radix Astragali and Radix Angelicae Sinensis treatment. Conclusions Radix Astragali and Radix Angelicae Sinensis could intervene in the immunologic balance of T lymphocytes, inhibit the apoptosis of BM cells induced by immune attack, restore the balance of the T cell immune response network and recover the hematopoietic function of HSCs. The synergistic effects of Radix Astragali and Radix Angelicae Sinensis were superior to those of each herb alone.